PPARα and γ Activation Effects of New Nor-triterpenoidal Saponins from the Aerial Parts of Anabasis articulata - Salah El Dine, Riham; Abdallah, Hossam M.; Kandil, Zeinab A.; Zaki, Ahmed A.; Khan, Shabana I.; Khan, Ikhlas A. (Planta Medica, 2019)
Anabasis articulata, traditionally used to treat diabetes, is rich in saponin content. This study was performed to investigate the agonistic effect of its saponins on peroxisome proliferator-activated receptor-α and peroxisome proliferator-activated receptor-γ in human hepatoma (HepG2) cells to explore the possibility of the involvement of these nuclear receptors in the mechanism of the antidiabetic effect of the plant. Chemical investigation of the n-butanol fraction resulted in the isolation of three new and one known 30-noroleanane triterpenoid saponins. The structures of the new compounds were elucidated as 3β-hydroxy,23-aldehyde-30-norolean-12,20(29)-dien-28-oic acid-28-O-β-D-glucopyranosyl ester (1), 3β-O-D-galactopyranosyl-23-aldehyde-30-norolean-12,20(29)-dien-28-oic acid-28-O-β-D-glucopyranosyl ester (2), and 3β-O-D-xylopyranosyl-30-norolean-12,20(29)-dien-28-oic acid 28-O-β-D-glucopyranosyl ester (3), while the known 30-nortriterpenoidal saponin was identified as boussingoside E (4). Although, the isolated saponins (1 – 4) did not show > 1.5-fold activation of peroxisome proliferator-activated receptor-γ, but two of them (1 and 3) activated peroxisome proliferator-activated receptor-α to the higher extents of 2.25- and 1.86-fold, respectively. These results suggest that the reported antidiabetic action of the isolated saponins may not solely involve the activation of peroxisome proliferator-activated receptor-γ. However, the agonistic activity of the n-butanol fraction of A. articulata (1.71-fold induction) and two of its saponins (1 and 3) towards peroxisome proliferator-activated receptor-α may be beneficial in the cardiovascular condition that is closely associated with diabetes and other metabolic disorders.
Keywords: PPARα; PPARγ; Anabasis articulata; antidiabetic; Amaranthaceae; triterpene saponins